Reduced levels of reactive oxygen species correlate with inhibition of apoptosis, rise in thioredoxin expression and increased bovine leukemia virus proviral loads - François Carole; Florins Arnaud; Boxus Mathieu; Bouzar Amel; Reichert Michal; Willems Luc (Retrovirology, 2009)
Abstract Background Bovine Leukemia virus (BLV) is a deltaretrovirus that induces lymphoproliferation and leukemia in ruminants. In ex vivo cultures of B lymphocytes isolated from BLV-infected sheep show that spontaneous apoptosis is reduced. Here, we investigated the involvement of reactive oxygen species (ROS) in this process. Results We demonstrate that (i) the levels of ROS and a major product of oxidative stress (8-OHdG) are reduced, while the thioredoxin antioxidant protein is highly expressed in BLV-infected B lymphocytes, (ii) induction of ROS by valproate (VPA) is pro-apoptotic, (iii) inversely, the scavenging of ROS with N-acetylcysteine inhibits apoptosis, and finally (iv) the levels of ROS inversely correlate with the proviral loads. Conclusion Together, these observations underline the importance of ROS in the mechanisms of inhibition of apoptosis linked to BLV infection.